2015
DOI: 10.1007/s12262-015-1261-4
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Intrahepatic Injection Iodine-131-Lipiodol Improves Prognosis of Patients with Hepatocellular Carcinoma After Resection: a Meta-Analysis

Abstract: High incidence of intrahepatic recurrence is a major surgical limitation following hepatectomy of hepatocellular carcinoma (HCC). This study was intended to investigate the effects of adjuvant intrahepatic injection of iodine-131-lipiodol on disease recurrence and survival in patients with HCC who underwent resection. A computerized literature search was performed to identify relevant articles. Data synthesis was performed using Review Manager 5.0 software, and results are presented as odds ratio (OR) with 95 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Another topic which is worth further study is adjuvant therapy. It was shown in several studies (19,20) that there might be potential benefit by adjuvant therapy, such as transcatheter arterial chemoembolization, in a selected group of patients who received curative resection. In a randomized controlled trial by Zhong et al (21), it was shown that hepatectomy with adjuvant TACE was able to improve both the OS when compared with hepatectomy alone in patients with Stage IIIA disease (UICC 6 th edition).…”
Section: Discussionmentioning
confidence: 99%
“…Another topic which is worth further study is adjuvant therapy. It was shown in several studies (19,20) that there might be potential benefit by adjuvant therapy, such as transcatheter arterial chemoembolization, in a selected group of patients who received curative resection. In a randomized controlled trial by Zhong et al (21), it was shown that hepatectomy with adjuvant TACE was able to improve both the OS when compared with hepatectomy alone in patients with Stage IIIA disease (UICC 6 th edition).…”
Section: Discussionmentioning
confidence: 99%
“…As the 5-year recurrence rate even after curative resection for HCC is very high at 50% to 70% (154531532), an effective adjuvant therapy is urgently required. Although many studies for adjuvant therapy after curative therapy in HCC through TACE (533), 131 I infusion via the hepatic artery (534), vitamin K 2 (535), and vitamin A analogue (536) have been performed, there is still no proven clinical significance (77). Cytotoxic systemic chemotherapy (537) and sorafenib (538) also have no clinical evidence for adjuvant therapy.…”
Section: Adjuvant Therapymentioning
confidence: 99%
“…A total of 334 patients were included. This study detected a statistical benefit for patients receiving I-131 lipiodol over the control group 15 . However, this drug is not approved by the FDA and is not available for use in the US and most countries.…”
Section: Resultsmentioning
confidence: 57%
“…A recent meta-analysis evaluated the results of two randomized clinical trials and three case-control studies evaluating the effects of the use of I-131 lipiodol transarterial (via hepatic artery) for tumor chemoembolization (TACE) 15 . A total of 334 patients were included.…”
Section: Resultsmentioning
confidence: 99%